Israel's Global Capitalism - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2004)
The flaring up of the Israeli-Palestinian conflict in the early 2000s caught most experts by surprise. The 1990s euphoria of the Oslo `peace process' suddenly dissipated, replaced by a second intifada; the newspeak of `peace dividends' gave way to debates about `imperialism'; and instead of `global villageism' there is now much talk about the `war on terrorism.' Interestingly, most analysts, popular as well as academic, seem to view this dramatic change largely as a `chance occurrence.' In a world dominated by postmodern `narrative' and `discourse,' nothing is truly `real' – or alternatively, the only `reality' is what we see on television and read in the newspapers. According to the media, the Israeli-Palestinian conflict, like all conflicts, is a matter of ethnicity, religion and culture, and these sentiments have their ups and downs. The prime agitators of such sentiments are `leaders' of various kinds – state officials, army generals, spiritual figures and religious icons – whose clashing urges produce different outcomes. In the present conjunction, the shift from peace to war was triggered by Israel's far right, which, led by Benjamin Netanyahu and Ariel Sharon, decided to derail the fragile Oslo Accord in order to continue the settlement of Greater Israel. Unfortunately, so far there has been little attempt to go beyond these immediate appearances. History certainly is open-ended, but it is not random. And while ethnicity, religion and culture are real features of our capitalist world, they cannot adequately explain its development. Israel is a capitalist country in a capitalist world, and therefore its history – including its conflict with the Palestinians – needs to be situated within the broader processes of capitalist development, local and global. Focusing on the 1990s, the purpose of this paper is to identify several key developments in global capitalism, examine how these processes altered the political economy of Israel and speculate on what they may mean for the future.
Keywords: 330; accumulation; acquisitions; capital; capitalism; centralization; competition; conflict; conglomeration; corporation; crisis; development; distribution; dual economy; elite; energy; finance; globalization; growth; distribution; institutionalism; high-tech